PERAN GENDET DALAM AGROINDUSTRI BOLU KEMOJO DI KOTA PEKANBARU - Aulia Muhaimin; Rosnita Rosnita; Shorea Khaswarina (Indonesian Journal of Agricultural Economics, 2020)
This research aims to 1) to know the profile of shrimp boilers agroindustry, 2) to know the allocation of male and female work time related to reproduction, productive and social, 3) to know the role of man and woman in decision making in the household. Data taken by survey method. Respondents in this study were taken by purposive sampling with the criteria of men and women have married as the owner of bolu kemojo agroindustry consisting of 4 partner owners from 4 agroindustry. Data were analyzed by quantitative descriptive method and Likert Summated Rating (SLR) Scale. The results showed that the total allocation of men's time was 852.16 hours / month and the woman was 468.39 hours / month. In reproductive activities men's time allocation is 29.96 hours / month and women is 170.36 hours / month, compared with men's productive activities of 816.20 hours / month and women of 293.28 hours / month. On social activities of 6.00 hours / month for men and 4.75 hours / month for women. Allocation of time beyond rest, worship and relaxation. In decision making in the household conducted by husband and wife shown by score 3.11